2021
DOI: 10.33086/mhsj.v5i2.2362
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Activity of Extract of Celery (Apium Graveolens) in Insilico Study

Abstract: Backround: Celery (Apium graveolens L., Apiaceae) is one of the medicinal plants with secondary metabolite components that have pharmacological effects such as vitamin (choline) content. This study aims to evaluate the mechanism and interaction of choline contained in celery on its effectiveness as a neuroprotective. Methods: This research is an experimental research using the in silico study. Results: The insilico search found that the choline content in celery binds to Slc5a7, Chat and Ache. Which has a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The insilico research showed the activity in the neurotransmitter secretion process, neurotransmitter biosynthesis process, and neurotransmitter metabolic process. It is reported that neuroprotective activity has been found in celery by the interaction of Ache, Slc5a7, and Chat [ 555 ]…”
Section: Health Benefit Potentialmentioning
confidence: 99%
“…The insilico research showed the activity in the neurotransmitter secretion process, neurotransmitter biosynthesis process, and neurotransmitter metabolic process. It is reported that neuroprotective activity has been found in celery by the interaction of Ache, Slc5a7, and Chat [ 555 ]…”
Section: Health Benefit Potentialmentioning
confidence: 99%